A Morphological Proces and Aspect of Naming Place at South Amurang - Vivi Nansy Tumuju; Vany Kamu; Tien Siamando (SOSIOEDUKASI, 2025)
Toponyms are not merely geographical labels but also linguistic repositories of cultural memory, historical experience, and environmental perception. In regions with rich ethno-linguistic diversity, such as South Minahasa, Indonesia, place-names reflect the intricate relationship between language, identity, and local knowledge. This study investigates the morphological structure and dominant naming themes of ten toponyms in South Amurang District, South Minahasa Regency, where the Tontemboan language is increasingly endangered. It addresses a critical gap in toponymic research by prioritizing linguistic morphology over narrative or historical speculation, offering a scientifically grounded interpretation of place-names. Employing a qualitative descriptive case study design, data were collected through field observations, in-depth interviews with 20 key informants, and the Simak Libat Cakap (SLC) technique. The analysis followed the intralingual matching method involving morphemic decomposition, lexical clarification, and contextual interpretation. The theoretical framework integrates Djajasudarma’s (1993) morphological theory and Duranti’s (1997) anthropological linguistics to balance structural and cultural analyses. The findings revealed that eight of the ten toponyms underwent morphological processes affixation, compounding, acronym formation, and complex affixation demonstrating a systematic naming system rooted in Tontemboan grammar. Water emerged as the dominant naming theme, appearing in four toponyms and reflecting its ecological and cultural centrality. Other themes included geographical features, community habits, historical events, and gratitude. Morphological analysis has successfully resolved long-standing community debates on names such as Pinalin and Malenos, confirming that linguistic decomposition yields more accurate meanings than oral narratives. This study concludes that morphological analysis is essential for valid toponymic interpretation, especially in regions with complex local languages. It offers a replicable model for integrating linguistic structure with the cultural context, contributing to language documentation, cultural preservation, and informed public policy.